PENGARUH PESAN KAMPANYE #GenZHeTikYuk! TERHADAP SIKAP RAMAH LINGKUNGAN PENGIKUT AKUN INSTAGRAM @dutalingkunganpku - Simamora, Dina Lestari; Lubis, Evawani Elysa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
GenZHeTikYuk Campaign Program! is a campaign to save the use of plastics (bottles, cups, bags, etc.) Which focuses on generation Z (born 1995-2012). The campaign was initiated by the Duta Lingkungan Pekanbaru who was selected by the Dinas Lingkungan Hidup dan Kebersihan Kota Pekanbaru to deliver environmental messages to Generation Z. The purpose of this study was to find out how much effect the #GenZHeTikYuk campaign message! towards the environmentally friendly attitude of followers of the account Instagram @dutalingkunganpku. The theory used in this research is the Stimulus-Response theory.Â This research uses quantitative research methods, with data collections techiques, namely through the distribution of questionnaires directly to followers of the Instagram account @dutalingkunganpku with a sample size of 100 respondents calculated using the Slovin formula and determined through purposive sampling technique. Data analysis tecniques in this study use simple linear regression analysis techniques that are processed using SPSS 21 for Windows.The results of this study indicate the value of the regression coefficient in this study is Y = 20,241 + 1,112 (X). The constant number (a) is 20,241 and the coefficient of variable X is 1,112. Meanwhile tcount (8.145) is greater than ttable (1.984). Based on statistical calculations obtained,the hypothesis for this study is Ha significant difference between the campaign message #GenZHeTikYuk! (X) towards the friendly attitude of followers of theaccount Instagram @dutalingkunganpku (Y). Then it means that Ha is accepted and H0 is rejected. Based on the correlation interpretation guidelines obtained the correlation coefficient (r) of 0.653, the relationship between the campaign message variable #GenZHeTikYuk! with an environmentally friendly attitude in the strong category. Furthermore, the coefficient of determination (Rsquare) is equal to 0.404. This means it can be explained that the friendly attitude of followers of the account Instagram @dutalingkunganpku by 40.4% is influenced by the #GenZHeTikYuk! Campaign message! while the rest is influenced by other variables not examined in this study